(untitled) - Huynh, Quang Tin (Wageningen, 2009)
This thesis report the study on rice seed and seed production training programme conducted in seven prvinces of Vietnam during the period 2003-2007. The object of this research was assess to what extent farmers's knowledge in seed production practices and seed quality management had increased and whether that knowledge increase was reflected in an creases in potentialrice yields and profits and in dissfusion of retained practices after training to other farmers in communities
Keywords: Seed productions,Sản xuất giống